1988
DOI: 10.1093/ee/17.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Flight Patterns of Phloem- and Wood-Boring Coleoptera (Scolytidae, Platypodidae, Curculionidae, Buprestidae, Cerambycidae) in a North Florida Slash Pine Plantation

Abstract: Sticky traps adjacent to severed and tipped slash pines and window traps with ethanol as attractant and collecting fluid (randomly located in the stand) were used to monitor flight patterns of Scolytidae, Platypodidae, Curculionidae, Buprestidae, and Cerambycidae in a slash pine plantation in North Florida. Forty-nine species were trapped, of which 35 breed in pines and 14 in hosts in the understory and nearby cypress domes. Sticky and window traps differed greatly with respect to species trapped, relative abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
2
10
0
2
Order By: Relevance
“…Similarly, other studies have found that greater numbers of A. planipennis, as well as other buprestids, are caught in the canopy as opposed to near the ground (Francese et al , 2008Wermelinger et al 2007) along with observations on beetle behavior in the field Lelito et al 2007a, b;RodriguezSaona et al 2007). Correlation between trap capture and the feeding, breeding, and dispersal habits of other beetle species is not uncommon (Atkinson et al 1988;Safranyik et al 2000).…”
Section: Host Volatiles-ash Seedlings and Foliagementioning
confidence: 99%
“…Similarly, other studies have found that greater numbers of A. planipennis, as well as other buprestids, are caught in the canopy as opposed to near the ground (Francese et al , 2008Wermelinger et al 2007) along with observations on beetle behavior in the field Lelito et al 2007a, b;RodriguezSaona et al 2007). Correlation between trap capture and the feeding, breeding, and dispersal habits of other beetle species is not uncommon (Atkinson et al 1988;Safranyik et al 2000).…”
Section: Host Volatiles-ash Seedlings and Foliagementioning
confidence: 99%
“…Currently there are no methods for protecting arboreal production against this pest. In addition, there are few methods of monitoring Buprestidae (Dunn et al, 1986) as traps provide erratic and variable information on the flight periodicity and the species present, and are therefore of little help in controlling the beetles (Atkinson et al, 1988;Markalas & Kalapanida, 1997;Fassotte, 1999;Morewood et al, 2002;Groot & Nott, 2003;Oliver et al, 2003;Miller, 2006). Dispersal in C. tenebrionis, as in other winged insects, besides mechanisms linked to human activity, is mainly dependent on long distance flights (Duan et al, 1998;Muirhead et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…173, July 1995 is in contrast to that often reported for most common species in temperate regions (Atkinson et al, 1988). This could probably be attributed to the fact that the occurrence and abundance of many insects are primarily determined by fluctuations in the availability of breeding materials in their habitats (Dempster and Pollard, 1981).…”
Section: Discussionmentioning
confidence: 86%